Application Database of Comprehensive Emergency Neonatal and Obstetric Service in Sampang Hospita - Andarini, Yenik Dyah; Hargono, Arief (Jurnal Berkala Epidemiologi, 2015)
ABSTRACTServices Comprehensive Emergency Obstetric and Neonatal Care (PONEK) is essential maternal and neonatal care/ emergency comprehensively which aims to save mothers and newborns. Activities PONEK in Hospital involving several service units where data maternal and neonatal services are sourced from each service unit, database shall be integrated data and information wich is needed. The purpose of this study was to develope database model PONEK. The scope includes the development of database PONEK include maternal and neonatal care int he Hospital. This research was conducted through qualitative approach to the type of research was action research that the development of database model. Development of database model PONEK system approached includes input, process and output. Subjects in this study was the Hospital Management Team and Officers PONEK Recording and Reporting Hospital Sampang. Analysis of recording and reporting system PONEK Sampang Hospital found some problems that the registers were not uniform formats, duplication of records, which is still manual data storage, process inautomation as well asa report that has not produced informationis still limited. Results of this study are prototype Database PONEK based on the information needs of maternal and neonatal care. PONEK database developed can generate the information needed by the team so that it can be used to PONEK performance monitoring and evaluation in the Hospital. Implementation of the database PONEK should be supported by the availability of appropriate computer specifications, human resources that qualified, maintenance management system and training toimprove reporting officers PONEK.Keywords: database, comprehensive emergency obstetrics and neonatal care, recording and reporting system